Endoglucanase production by endophytic fungi isolated from Vitis labrusca L. with peanut hull and sawdust as substrates - Felber, Aretusa Cristina; Specian, Vânia; Orlandelli, Ravely Casarotti [UNESP]; Costa, Alessandra Tenório [UNESP]; Polonio, Julio Cesar; Mourão, Káthia Socorro Mathias; Pamphile, João Alencar (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2019)
Endoglucanases are enzymes widely employed in different industrial fields, albeit with high production costs. Studies on new microbial sources and low-cost substrates are highly relevant, including those on agro-industrial. Current analysis evaluates peanut hull (PH) and sawdust (SD) as substrates for submerged cultures of 14 endophytic fungi isolated from grapevine (Vitis labrusca L.) cultivars Bordô and Concord. Endophytes were grown on a carboxymethylcellulose (CMC) medium and the cup plate assay showed that eight strains (belonging to genera Cochliobolus, Diaporthe, Fusarium and Phoma) had positive results: enzymatic halos ranged from 10.8±0.02 to 15.5±0.07 mm in diameter. Diaporthe sp. strains (GenBank accession codes KM362392, KM362368 and KM362378) and Fusarium culmorum KM362384 were highlighted as the most promising sources. Further, PH and SD as substrates for the fermentation of these fungi were evaluated by the cup plate assay and endoglucanase activity assay. Highest halo diameters were obtained for Diaporthe sp. KM362392: 16.1±0.01 mm (CMC), 14.5±0.01 mm (PH) and 14.7±0.03 mm (SD). The fungus also presented the highest levels of endoglucanase activity: analysis of variance revealed that CMC (3.52±0.98 µmol/min), PH (2.93±0.23 µmol/min) and SD (3.26±0.38 µmol/min) were similarly efficient as substrates. Results deepen knowledge on V. labrusca endophytes that may be endoglucanase sources, even though further optimizations in submerged cultures with PH and SD should be undertaken to increase the enzymatic production from these wastes.
Produção de endoglucanase por fungos endofíticos isolados de vitis labrusca L. utilizando casca de amendoim e serragem como substratos
Keywords: Agro-industrial wastes; Cellulase; Endophytes; Microbial enzymes; Submerged fermentation